2005
DOI: 10.1159/000084822
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neoadjuvant Chemotherapy in the Treatment of Advanced Ovarian Cancer

Abstract: Primary cytoreductive surgery followed by chemotherapy represents the current standard treatment for patients with advanced ovarian cancer. Neoadjuvant chemotherapy followed by interval debulking surgery has been proposed as an alternative approach for the initial management of bulky ovarian cancer, aiming at the improvement of surgical efficiency and patients’ quality of life. According to the hitherto published studies, consisting mainly of retrospective observations, neoadjuvant chemotherapy followed by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Many authors have reported an optimal cytoreduction rate of 60-75% following NACT in nonrandomized trials. [13][14][15][16] In our study, optimal cytoreduction rate was 72%, which is similar to that reported in the literature using NACT. The surgical cytoreduction was 100% in patients with clinical and radiological complete response, 84% in patients with partial response and 0% in patients with no response to NACT.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Many authors have reported an optimal cytoreduction rate of 60-75% following NACT in nonrandomized trials. [13][14][15][16] In our study, optimal cytoreduction rate was 72%, which is similar to that reported in the literature using NACT. The surgical cytoreduction was 100% in patients with clinical and radiological complete response, 84% in patients with partial response and 0% in patients with no response to NACT.…”
Section: Discussionsupporting
confidence: 87%
“…Initial reports of NACT in advanced ovarian cancers have reported a response rate of 70-80% [13,15,16] and an acceptable toxicity profile. [27,28] In our study, all patients could complete planned NACT with acceptable toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a poor prognosis in the advanced stages and responds poorly to conventional chemotherapy (paclitaxel/carboplatin) (Kurman and Seidman, 2000;Hess et al, 2004;Gurung et al, 2013). An efficient treatment is not yet available (Pectasides et al, 2005).…”
Section: Introductionmentioning
confidence: 99%